PENGARUH DESTINATION PER SONALITY TERHADAP REVISIT INTENTION MELALUI BEHAVIORAL INTENTION SEBAGAI VARIABEL MEDIASI DALAM PERSPEKTIF BISNIS ISLAM (Studi Pada Pengunjung Curup Gangsa Kasui Way Kanan) - Jemi Karter; Suhendar Suhendar; Heni Verawati (JURNAL LENTERA BISNIS, 2025)
Indonesia is a country with many beautiful and stunning natural resources. Curup Gangsa Waterfall is one of them. However, Curup Gangsa Waterfall has experienced a decrease in visitors in the last 2 years. This is because few people return there. This study aims to determine: 1) Does Destination Personality affect the Revision Intention of visitors to Curup Gangsa Waterfall Kasuy Way Kanan? 2) Does Destination Personality affect the Behavioral Intention of Visitors to Curup Gangsa Waterfall Kasuy Way Kanan? 3) Does Behavioral Intention Affect the Revisit Intention of Visitors to Curup Gangsa Waterfall Way Kanan? 4) Can Behavioral Intention mediate the influence between Destination Personality on the Revisit Intention of Visitors to Curup Gangsa Waterfall Way Kanan? 5) What is the view in Islamic business about Behavioral Intention Mediating Destination Personality on the Revisit Intention of Visitors to Curup Gangsa Waterfall Way Kanan? This research is a researchfield researchwith a quantitative method carried out on 100 visitors to the Curup Gangsa Kasuy Way Kanan waterfall which was determined using the methodpurposive sampling. The data obtained were processed using SmartPLS 3 with Validity Test and Hypothesis Test. The results of the study indicate that: 1) Destination Personality has a positive and significant effect on revisit intention, 2) Destination Personality has a positive and significant effect on behavioral intention, 3) Behavioral Intention has a positive and significant effect on revisit intention, 4) Behavioral Intention partially mediates the relationship between Destination Personality and Revisit Intention, 5) The behavior of tourists visiting the Curup Gangsa Kasuy Way Kanan waterfall is in accordance with the perspective of Islamic business. This is because they visit to enjoy the natural beauty in it and not to damage and maintain the sustainability of the waterfall. Likewise, their behavior in recommending the Curup Gangsa waterfall to others who are honest, do not exaggerate and do not badmouth the tourist attractions in it.